Gamified Podcast-Based Learning for Improving Listening Comprehension, Motivation, and Retention in EFL Students - Iis Susiawati; Arozatulo Bawamenew; Zohaib Hassan Sain (Global Education : International Journal of Educational Sciences and Languages, 2024)
The rapid development of technology has introduced various language learning resources, including podcasts, which offer authentic audio input but are often underutilized and lack structured application in EFL classrooms. Integrating gamification into podcasts represents a promising approach to enhance students’ engagement, motivation, and learning outcomes. This study aims to evaluate the impact of gamified podcasts on EFL students’ listening comprehension, learning motivation, and content retention. A quasi-experimental design was employed, involving university-level EFL students divided into an experimental group (gamified podcasts with interactive quizzes, leaderboards, and badges) and a control group (non-gamified podcasts). Pre-tests and post-tests assessed listening comprehension, motivation, and retention, with statistical comparisons conducted using t-tests and ANOVA. The results indicate that students exposed to gamified podcasts demonstrated significant improvements in listening comprehension, motivation, and retention compared to their peers in the control group. The interactive and competitive elements of gamification encouraged repeated engagement, active participation, and deeper cognitive processing of audio materials, which strengthened long-term memory and overall learning outcomes. These findings suggest that gamified podcast-based learning not only enriches traditional listening practices but also fosters a more engaging, motivating, and effective EFL learning environment. Consequently, integrating gamification into podcast instruction is recommended as an innovative strategy to support language acquisition and enhance students’ sustained involvement in learning activities.